Penerapan Ekstraksi Cair Tekanan Uap Tinggi Menggunakan Bahan Halal untuk Optimasi Antioksidan - Hasan, Akhmad Endang Zainal; Wiendarlina, Ike Yulia; Witdiastuti, Witdiastuti (JURNAL AGROINDUSTRI HALAL, 2022)
Soursop is a plant that is used as traditional medicine. Antioxidants are compounds that are able to delay, slow down, or inhibit oxidation reactions. This study aims to determine the effect of variations in extraction time and the comparison of variations in the amount of simplicia with aquadest solvent on the high pressure extraction method on antioxidant activity. The study made 13 treatments using the Response Surface Methodology (RSM) design with the fit of the Central Composite Design (CCD) model. The results showed that from the 13 treatments, the extraction time had an effect on the percent yield with the equation Y = -51.9692 + 24.2030 X1 + 1.2984 X2. The extraction time (X1) has a value greater than the ratio of simplicia powder to the volume of distilled water (X2) as well as the IC50 value as shown in the equation Y = 171,983 + 13,828 X1 – 4,110 X2. Extraction time (X1) has a greater value when compared to simplicia with aquadest solvent volume (X2). The results of the analysis of the percentage of extract yield and the optimal IC50 value using RSM analysis were thought to have an extraction time of 6.3 minutes and the ratio of simplicia powder to the volume of aquadest solvent was 1:61,2. The results of the antioxidant activity obtained that the optimal IC50 value was estimated at 4.3 minutes of extraction time and the ratio of simplicia powder to the volume of aquadest solvent was 1:78.2.